PT Angkasa Gema Nusantara Wedding Vendor Marketing Strategy to Build Customer Interest - Kasanah, Riski Dwi; Zulistiani (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this study is to identify marketing strategies, internal and external environmental conditions and analyze the most effective strategies in marketing.build customer interest. Design/Method/Approach : Data collection uses a qualitative approach, data collection uses observation, interview and documentation techniques and data analysis used is descriptive analysis techniques. By applying informant selection techniques according to 5R (relevance, recommendation, rapport, readiness, reassurance). Research Findings : To evaluate the strengths, weaknesses, opportunities and threats faced by the company. The findings show that the main strengths lie in the quality of service and relatively affordable prices, while weaknesses include limited marketing budget and quite expensive transportation. Opportunities arise from the increasing use of social media as a promotional platform, while threats come from tight competition in the wedding industry. Theoretical contribution/Originality : There has not been much research in the area related to wedding vendors. Practitionel/Policy implications :Useful as a way to increase customer interest. Research limitations : The limitations of this study include sampling only from this company, so the results cannot be generalized to other vendors.